On solutions of hyperbolic differential inclusions with nonconvex right-hand side - Vityuk, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
The existence of a generalized solution with continuous derivativesu x ,u y is proved for the differential inclusionu xy ∈F(x, y, u) with a nonconvex right-hand side satisfying the Lipschitz conditioninx, y, andu.